A Note on PhD Population Growth in Biomedical Sciences. (21st November 2014) - Ghaffarzadegan, Navid; Hawley, Joshua; Larson, Richard; Xue, Yi
<x xml:space="preserve">Abstract</x> The explosive increase in the number of postdocs in biomedical fields is puzzling for many science policymakers. We use our previously introduced parameter in this journal, the basic reproductive number in academia (R0), to make sense of PhD population growth in biomedical fields. Our analysis shows how R0 in biomedical fields has increased over time, and we estimate that there is approximately only one tenure‐track position in the US for every 6.3 PhD graduates, which means that the rest need to get jobs outside academia or stay in lower‐paid temporary positions. We elaborate on the structural reasons and systemic flaws of science workforce development by discussing feedback loops, especially vicious cycles, which contribute to over‐production of PhDs. We argue that the current system is unstable but with no easy solution. A way to mitigate the effects of strong reinforcing loops is full disclosure of the risks of getting PhD. © 2014 The Authors. Systems Research and Behavioral Science published by John Wiley & Sons Ltd.